Climate and land use changes in relation to runoff variability in the Kelantan River Basin using SCS-CN and geospatial technology - Ahmad Shafuan, Mohammad Faizalhakim (2017)
Increasing magnitude and frequency of catastrophic natural disasters such as floods proves that climate change is unequivocal. It is related to prolonged and extreme rainfall (>500ARI), in addition to massive land use conversion that contributed to severe flooding in 2014. To clarify the local debate on causes of flooding, this study integrates SCS-CN and geospatial analysis to investigate the effects of land use and climate change on runoff based on historical data from 1984 to 2014 in the Kelantan River Basin. From 1984 to 2014, the climate in Kelantan River Basin is discovered increasing trends in terms of rainfall (41.13 mm year-1), rain days (1.58 days year-1) and temperature (0.07°C year-1). While, the rates of deforestation in Kelantan River Basin was 8,870 ha year-1 and an expansion of rubber and oil palm plantations was 1,480 and 4,060 ha year-1, respectively. It is resulting to gradual increase by 120 and 164% in the estimated runoff using SCS-CN in the Kelantan River Basin on 2004 and 2014, respectively. The results suggest that steady deforestation and gradual expansion of oil palm and rubber plantation, as well as global and localised climate change, intensified the runoff generation in the basin. The correlation analysis suggests that the climate change as being more influential than land use changes towards runoff generation. While the SCS-CN method on a localised scale revealed that large agriculture expansion is a major contributor to runoff, as compared to rainfall events. The extensive land clearing areas found in the hilly areas, unclear buffer zone, poor soil conservation practices and poor drainage system as the contributors to high potential runoff areas (i.e. Gua Musang, Lojing, Pergau, Kuala Betis, Jeli, Kuala Krai and Kota Bharu) are among the factors contributing to high runoff. Integrated land use management and river basin management approach should be extensively implemented to lessen the consequences on the environment while maximising the benefit to economic and social aspects.